Karakteristik dan Problematika Pembelajaran bahasa Arab untuk Tujuan Khusus - Ainur Ridho (Jurnal Pendidikan Bahasa Arab, 2024)
This article aims to examine the characteristics and uniqueness of the curriculum or teaching methods of Arabic for specific purposes, as well as to examine the issues and challenges in its implementation in the learning process. This study is expected to assist Arabic language instructors in implementing this curriculum or teaching method for specific purposes. The article uses a qualitative descriptive approach with literature review and istiqro'i analysis methodology from various sources discussing the curriculum or teaching methods of Arabic for specific purposes, such as books, journals, and others. The author then consolidates them into a comprehensive discussion. The results of this study indicate that the curriculum for teaching Arabic for specific purposes has various characteristics that differ from other curricula, as well as challenges in its implementation.